Patient experience of opioid use disorder treatment medications: a systematic review of contemporary qualitative research - Luke Mitcheson; John Marsden; Natalie Lowry; Mike Kelleher; Carina Najia (BMJ Open)
Objectives Opioid agonist, partial agonist and antagonist medications are used to treat opioid use disorder (OUD). This was the first omnibus narrative systematic review of the contemporary qualitative literature on patient experiences of receiving these medications.Design Narrative systematic review using the sample, phenomenon of interest, design, evaluation and research framework.Data sources PubMed, Embase and APA PsycINFO were searched between 1 January 2000 and 14 June 2023, with the addition of hand searches.Eligibility criteria for selecting studies Qualitative and mixed methods studies among adults with experience of receiving OUD treatment medication in community and criminal justice settings.Data extraction and synthesis One reviewer conducted searches using the pre-registered strategy. Two independent reviewers screened studies and assessed quality using the Consolidation Criteria for Reporting Qualitative tool. Identified reports were first categorised using domains from the addiction dimensions for assessment and personalised treatment (an instrument developed to guide OUD treatment planning), then by narrative synthesis.Results From 1129 studies, 47 reports (published between 2005 and 2023) were included. Five major themes (and nine subthemes) were identified: (1) expectations about initiating treatment (barriers to access; motivations to receive medication); (2) responses to medication induction and stabilisation; (3) experience of the dispensing pharmacy (attending; medication dispensing); (4) experiences of maintenance treatment (services; dose adjustment; personal and social functioning); and (5) social factors (integration and stigma) and experiences of discontinuing treatment. Together these themes reflected and endorsed the importance of patient-centred care and clinically integrated services. Further qualitative research in real-world settings is needed on extended-release buprenorphine given the relative novelty of this medication option.Conclusions A narrative systematic review of the qualitative studies of medications for OUD endorsed the importance of patient-centred care and clinically integrated services.PROSPERO registration number CRD42019139365.